New Strategies for Enhancement of Infant Milk Formulas Composition - Irina A. Belyaeva; Elena P. Bombardirova; Tatiana V. Turti ("Paediatrician" Publishers LLC, 2023)
This article covers the issues of remodeling breast milk's protective properties during creating infant milk formulas. First of all, this concerns the conditions for normal intestinal microbiota development in growing organism. Its quantitative and qualitative features are the trigger of either sanogenetic, or pathological immune and metabolic reactions, and also determine gut-brain axis functioning. The protective significance of prebiotic composition diversity of mammalian milk and the inductive role of breast milk oligosaccharides are shown. The modern concept of synbiotics role in gastrointestinal tract and other systems functioning, as well as the use of modern synbiotics in the creation of infant formulas (available Russian formula included) are presented.